(untitled) (Journal of Innovative Research, 2025)
The emerging technology in education has been the current state of Artificial Intelligence (AI) in the education system, which is transforming teaching and learning systems and offering new opportunities of personalised learning, engagement, and achievement of student. This paper discusses how AI-assisted teaching can impact the experiences of students through items including personalization of learning, student engagement, self-efficacy, academic performance, and issues of ethics. Qualitative research design was embraced and data was gathered with the help of 25 participants who were students and educators with hands-on experience of AI in education. To elicit common patterns and themes, thematic analysis using six-volume guide steps according to Braun and Clarke (2006) was used. The results indicated that AI tools have the potential to improve personalization that complements the individual needs design, engagement by using gamification and immediate feedback, and increasing self-efficacy through scaffolding and training in safe-to-fail conditions. Moreover, participants stated that there has been an objective improvement in the academic achievements and the formation of digital literacy skills. Nevertheless, ethical issues, data privacy, algorithm bias, and access gaps were also expressed in concern during the study. The study argues that AI’s effectiveness in education is not solely based on its technological efficiency, but also on its ability to collaborate with human teachers, promoting balanced integration, fair access, and ethical protection.